The myelin protein PMP2 is regulated by SOX10 and drives melanoma cell invasion. (21st December 2018) - Graf, Saskia Anna; Heppt, Markus Vincent; Wessely, Anja; Krebs, Stefan; Kammerbauer, Claudia; Hornig, Eva; Strieder, Annamarie; Blum, Helmut; Bosserhoff, Anja‐Katrin; Berking, Carola
Abstract: The transcription factor sex determining region Y‐box 10 (SOX10) plays a key role in the development of melanocytes and glial cells from neural crest precursors. SOX10 is involved in melanoma initiation, proliferation, invasion, and survival. However, specific mediators which impart its oncogenic properties remain widely unknown. To identify target genes of SOX10, we performed RNA sequencing after ectopic expression of SOX10 in human melanoma cells. Among nine differentially regulated genes, peripheral myelin protein 2 ( PMP2 ) was consistently upregulated in several cell lines. Direct regulation of PMP2 by SOX10 was shown by chromatin immunoprecipitation, electrophoretic mobility shift, and luciferase reporter assays. Moreover, a coregulation of PMP2 by SOX10 and early growth response 2 in melanoma cells was found. Phenotypical investigation demonstrated that PMP2 expression can increase melanoma cell invasion. As PMP2 protein was detected only in a subset of melanoma cell lines, it might contribute to melanoma heterogeneity.